Recommendations on the Echocardiographic Assessment of Aortic Valve Stenosis: A Focused Update from the European Association of Cardiovascular Imaging and the American Society of Echocardiography - Baumgartner, Helmut; Hung, Judy; Bermejo, Javier; Chambers, John B; Edvardsen, Thor; Goldstein, Steven; Lancellotti, Patrizio; LeFevre, Melissa; Miller, Jr, Fletcher; Otto, Catherine M (Journal of the American Society of Echocardiography, 2017)
Echocardiography is the key tool for the diagnosis and evaluation of aortic stenosis. Because clinical decision-making is based on the echocardiographic assessment of its severity, it is essential that standards are adopted to maintain accuracy and consistency across echocardiographic laboratories. Detailed recommendations for the echocardiographic assessment of valve stenosis were published by the European Association of Echocardiography and the American Society of Echocardiography in 2009. In the meantime, numerous new studies on aortic stenosis have been published with particular new insights into the difficult subgroup of low gradient aortic stenosis making an update of recommendations necessary. The document focuses in particular on the optimization of left ventricular outflow tract assessment, low flow, low gradient aortic stenosis with preserved ejection fraction, a new classification of aortic stenosis by gradient, flow and ejection fraction, and a grading algorithm for an integrated and stepwise approach of aortic stenosis assessment in clinical practice.